Current non surgical management of uveal melanoma - Eman Said Zaid Turky; Mahmoud Salah Mostafa; Mohammed Abdalmoneim Hassaballah; Mohammed Mahmoud Alsaed (Cairo : Eman Said Zaid Turky, 2009)
Uveal melanoma is the most common primary malignant intraocular tumor in adults . It arises from melanocytes of uveal tract and most commonly affects the choroid . Choroidal melanoma has a high incidence of metastasis with an overall mortality rate up to 50% in 10years . In this work we will discuss current non surgical management in treatment of uveal melanoma which includes transpupillary thermotherapy photocagulation cryotherapy brachytherapy with various isotopes and external beam radiotherapy photodynamic therapy and sterotactic radiosurgery including Gamma Knife sterotactic radiosurgery (GKS)
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Ophthalmology
Issued also as CD
Keywords: Brachytherapy; Photocagulation; Transpupillary thermotherapy (TTT)